A systematic literature review of unhealthy food and beverage sport sponsorships in New Zealand : examining what existing discourse can tell us about the future : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, Auckland, New Zealand - Stevenson, Sumithrie Sasha (Massey University, 2023)
Background: Obesity and its related diseases are trending upward in New Zealand exacerbated by unhealthy food environments, overconsumption of unhealthy food and beverages, and pervasive marketing that promotes unhealthy food and drinks. Such marketing is frequently sought in the form of sport sponsorship and marketing through sport. Aim: This systematic literature review investigated the discourse in academic and grey literature from 1997-2022 regarding unhealthy food and beverage companies' sport sponsorships in New Zealand. Methodology: Literature searches were conducted in Google, Google Scholar, Discover, PubMed, Scopus, SPORTDiscus, Newztext, Factiva, Radio New Zealand, 1News, The New Zealand Herald, Stuff, Sport New Zealand, National Sport Organizations, New Zealand Legislation, the Advertising Standards Authority, and various websites using key search terms. Identified literature was documented according to those containing sport sponsorship (and associated) terms. The literature was analyzed and synthesized. Results: Sport sponsorships offered by unhealthy food and beverage companies are exacerbating the rising obesity rates in New Zealand. Opposition to unhealthy food and beverage company advertising, and sport sponsorships has increased in the last 25 years. New Zealand’s neoliberal government opposed marketing regulations favoring nutrition education, physical activity promotion, and unhealthy food and beverage company self-regulation via the Advertising Standards Authority voluntary codes. Studies found government and food and beverage companies’ anti-obesity measures ineffective and inadequate to curb unhealthy food and beverage marketing, including sponsorships. Such sport sponsorships normalize and promote unhealthy food and beverage consumption leading public health experts to recommend the regulation of these sponsorships. Conclusion: A multi-focused approach which includes government regulation of unhealthy food and beverage advertising, marketing and sport sponsorships is recommended. In the absence of such regulations, sport sponsorships seem likely to continue promoting unhealthy food and beverage consumption contributing to obesity in New Zealand.
Keywords: 470107 Media studies; 321005 Public health nutrition